Optimalisasi Pengelolaan Media Sosial sebagai Strategi Pemasaran Digital dalam Upaya Pengembangan Desa Kebontunggul Mojokerto sebagai Desa Wisata - Rizqi, Muchamad (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Social media has now become one of the digital marketing strategies considered quite effective, especially in the context of developing tourism potential in villages. Lembah Mbencirang, located in Kebontunggul Village, Gondang Subdistrict, Mojokerto Regency, is currently the main tourist attraction of Kebontunggul Village. However, the tourism promotion at this location is considered less than optimal due to several factors, including the lack of facilities and infrastructure to support the production of audiovisual content used as a means of tourism marketing through social media, resulting in less attractive photos and videos. The method used involves providing training and assistance in content creation for Instagram. Through Instagram, various information about tourism potential and community activities in Lembah Mbencirang can be widely accessed by both local communities and potential tourists. By utilizing features such as videos, images, and stories, social media managers can create engaging narratives that persuasively attract the attention and interest of people to visit Lembah Mbencirang. The use of Instagram as a social media platform is an effective digital marketing strategy to promote local tourism potential, such as Lembah Mbencirang in Kebontunggul Village, Mojokerto, which has the potential to drive economic growth and community development.